The Effect of Different Curing Methods on Concrete Strength - Dahlia Patah; Amry Dasar; Poppy Indrayani (Universitas Sulawesi Barat, 2022)
This study discusses the effect of method and age of treatment on increasing the strength of normal concrete in a tropical environment. A total of forty-five (45) concrete cylinders were treated with five different treatment methods, namely immersion in fresh water, immersion in sea water, wrapped in wet burlap sack, wrapped in plastic, and flushed with plain water. For each of these treatment methods, the average compressive strength of 3 cylinders of concrete was taken for each treatment period of 7, 28 and 91 days. The results showed that the immersion method with fresh water produced concrete specimens with the highest 28 day compressive strength of 42.99 N/mm2 followed by treatment with plastic wrap with a value of 40.94 N/mm2. It was found that the method of wrapping in burlap sacks at the initial age of cement hydration obtained a higher compressive strength than all immersion methods. And for the long term, concrete strength increased up to 19% with the method of treatment immersed in seawater and treatment with fresh water on the concrete strength at the age of 28 days.